Identification and Decomposition of Five Dominant Wild plants from Acid Swampland in South Sumatra - Siti Masreah Bernas; Andi Wijaya; Effendy Sagala Parlindungan; Siti Nurul Aidil Fitri (JOURNAL OF TROPICAL SOILS, 2015)
There were five emergence plants in swampland such as Polygonum barbatum, Neptunia prostrata, Phragmites karka, Ludwigia adscendens and Phragmites communis, which might be used for compost source, all the plants were easily adapted and grew very well on acid soil.  These plants were choosen because of abudancy and size. All plants were identified, collected, chopped and weighted then put in a 50 liters plastic drum for decomposting during 12 weeks. Composts temperature were monitored every week, nutrients content (N, P, K, Ca, Mg, Na) and compost chemical properties (C-organic, C.E.C., C/N ratio) were analysed every two weeks. Results showed that each compost from different plant varied in nutrients content and chemical properties.  Compost made of Neptunia prostata Lam. contained highest nutrients than others, it’s nutrients were N (4%), P (1675 mg kg-1), K (5.6 %), Ca (0.32 %), Mg (0.32 %) and Na (0.12 %) and the lowest nutrients content showed by compost of Phragmites karka Retz. in which N (2.4 %), P (1160 mg kg-1), K (2.62 %), Ca (0.04 %), Mg (0.07 %), and Na (0.03 %).  It seem broadleaf plants tended to have higher nutrients content than grasses or graminae. Neptunia prostrata compost had a high N content due to it’s leguminosae plant. Al and Fe were low in all composts, therefore all plants were recommended for organic nutrient sources. [How to Cite: Siti MB, A Wijaya, EP  Sagala  and SNA  Fitri. 2015. Identification and Decomposition of  Five Dominant Wild plants from Acid Swampland in South Sumatra. J Trop Soils 20: 149-155. Doi: 10.5400/jts.2015.20.3.149]